Analisis Pengembangan Kurikulum di Lembaga Pendidikan Islam pada Masa New Normal - Anri Naldi; Nurdila Nasution (Fitrah: Journal of Islamic Education, 2022)
This study aims to analyze curriculum development in Islamic educational institutions during the new normal period, focusing on curriculum changes, curriculum development in learning, and curriculum development outcomes. The research was carried out at MIS Elsusi Meldina because the madrasah has changed its curriculum. The research method used is qualitative with a case study approach. Collecting data using observation techniques, interviews, and documentation studies. Observations to observe learning activities by teachers and students, interviews to obtain data about the basis and development carried out by madrasa heads, and documentation used to analyze various policy documents related to curriculum development. The study results revealed that the curriculum changes occurred from the 2013 curriculum to the Free Learning Curriculum. The implementation of Islamic education in the new normal era is based on religious and general subjects and contains extracurricular materials with an Islamic education approach. The results achieved by students are mastering two knowledge at once and this development has given a different color from the learning in madrasas in general in the city of Medan.